Taxonomy of the leafhopper genus Drabescus Stål (Hemiptera: Cicadellidae: Deltocephalinae) with description of two new species from China - Xu, Deliang; Zhang, Yalin (Zootaxa, 2023)
Two new species from China, Drabescus macrocladus sp. nov. and Drabescus mucronatus sp. nov., are described and figured. An updated checklist with distributions and key to males of the species in this genus from China is given. The type specimens of these two new species are deposited in the Entomological Museum, Northwest A&F University, Yangling, Shaanxi, China (NWAFU) and in Sun Yat-Sen University (Zhongshan University, ZSU), Guangzhou, Guangdong, China.